PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PENYELENGGARAAN TILANG ELEKTRONIK DI KOTA BANDUNG - Ayyil Basyar; Engkus Engkus; Mohamad Ichsana Nur (Sekolah Tinggi Pariwisata Mataram, 2022)
The implementation of electronic ticketing is an innovation issued by the police. Electronic ticketing aims to minimize the occurrence of irregularities in law enforcement for traffic violations. In addition, electronic ticketing aims to facilitate services so that they can be maximized and avoid complicated procedures. This study aims to determine the application of good governance principles in the implementation of electronic ticketing in the city of Bandung. This study uses a descriptive type with a qualitative approach. Data collection techniques were carried out by interview and observation methods. The data was obtained from informants from the West Java Regional Police who collected three people and three people from the community. The results of this study are that the implementation of good governance in the implementation of electronic ticketing in the city of Bandung has not been maximized. This is evidenced by the presence of electronic ticket locations that do not operate. Socialization on the implementation of electronic ticketing in the city of Bandung is also not maximized. In addition, in the implementation of electronic ticketing in the city of Bandung, there are still many wrong targets.